String Theory Explanation of Galactic Rotation Found Using the Geodesic Constraint - Mark D. Roberts (Advances in High Energy Physics)
The unique spherically symmetric metric which has vanishing Weyl tensor, is asymptotically de-Sitter, and can model constant galactic rotation curves is presented. Two types of field equations are shown to have this metric as an exact solution. The first is Palatini varied scalar-tensor theory. The second is the low energy limit of string theory modified by inclusion of a contrived potential.